2008
DOI: 10.1103/physrevd.78.025021
|View full text |Cite
|
Sign up to set email alerts
|

Perfect magnetic conductor Casimir piston ind+1dimensions

Abstract: Perfect magnetic conductor (PMC) boundary conditions are dual to the more familiar perfect electric conductor (PEC) conditions and can be viewed as the electromagnetic analog of the boundary conditions in the bag model for hadrons in QCD. Recent advances and requirements in communication technologies have attracted great interest in PMC's and Casimir experiments involving structures that approximate PMC's may be carried out in the not too distant future. In this paper, we make a study of the zero-temperature P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…Imposing Dirichlet boundary conditions, as L → ∞ it is shown that the piston is attracted to the nearest end of the box. Higher-dimensional pistons have been considered with various boundary conditions [11,14,28,29,38,39,42]. Hertzberg et al showed that in three dimensions for perfect metallic boundary conditions the rectangular piston is attracted to the closest base [28,29]; for pistons with rectangular cross sections and Dirichlet or Neumann boundary conditions see also [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Imposing Dirichlet boundary conditions, as L → ∞ it is shown that the piston is attracted to the nearest end of the box. Higher-dimensional pistons have been considered with various boundary conditions [11,14,28,29,38,39,42]. Hertzberg et al showed that in three dimensions for perfect metallic boundary conditions the rectangular piston is attracted to the closest base [28,29]; for pistons with rectangular cross sections and Dirichlet or Neumann boundary conditions see also [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Before closing this section let us briefly comment on the regularization dependence of the force corresponding to the pistons we used. We shall make use of a cutoff parameter λ in the Casimir energy, in order to see explicitly the cancellation of the surface terms we mentioned in the introduction [11,25,27,26,16,17,18,19]. We work again for the piston 2 configuration.…”
Section: Semi-analytic Analysis For the Piston Casimir Forcementioning
confidence: 99%
“…However there is no reason to justify the loss of the surface term within the cutoff regularization technique. The Casimir piston solves this problem in a very nice way, because the surface terms of the two piston chambers cancel and thus the Casimir force can be consistently calculated [8,25,27,26,7,3,2,10,16,17,18,19]. We shall use the zeta-function regularization technique and also treat the problem numerically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are led to a Casimir piston model in which spacetime is flat. This model has attracted considerable attention in the recent literature [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. One reason for the current interest is obviously the mathematical elegance of the formalism; the efficiency of regularization procedures like the zeta function regularization is quite striking.…”
Section: Introductionmentioning
confidence: 99%